Evaluación de la empatía en alumnos de medicina humana de una universidad privada del Perú - Huarcaya-Victoria, Jeff (2019)
Abstract: Objectives To determine the levels of empathy in the medical students of the Universidad de San Martin de Porres (FMH-USMP), and its correlation with personal, sociodemographic and religious variables. Materials and methods Observational and cross-sectional study was performed with data obtained using the Jefferson Medical Empathy Scale (EEMJ), the Religious Attitude Scale (EAR), and a questionnaire of sociodemographic values. They were completed by total of 693 students of the FMH-USMP from the 1st to 6th year. Convenience sampling was used. Results The mean score of empathy levels was 109.03. Significantly higher levels of empathy were found in women (P < .0005); those who plan to follow a specialty ‘linked to the patient’ (P = .008); and in students who reported having a profession modelled on the treatment of the patient (P = .007). In the first three years of study, the levels of empathy gradually decreased. Variations in levels of empathy in each year were significant in women (P = .016). A correlation was found between the EEMJ and the EAR (r = 0.16, P < .0005). Conclusions Higher levels of empathy were observed in students who plan to follow a specialty ‘linked to the patient’, as well as women and those who reported having a profession modelled on treating the patient. Longitudinal studies should be conducted, with the aim of evaluating the evolution of medical empathy in medical students, as well as including empathy training in the curriculum design.